2015
DOI: 10.1039/c4cp05993j
|View full text |Cite
|
Sign up to set email alerts
|

Competition between electron transfer, trapping, and recombination in CdS nanorod–hydrogenase complexes

Abstract: Electron transfer from photoexcited CdS nanorods to [FeFe]-hydrogenase is a critical step in photochemical H2 production by CdS-hydrogenase complexes. By accounting for the distributions in the numbers of electron traps and enzymes adsorbed, we determine rate constants and quantum efficiencies for electron transfer from transient absorption measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(114 citation statements)
references
References 29 publications
10
103
1
Order By: Relevance
“…As hot e − relaxation in Cd-chalcogenide quantum dots occurs in the subpicosecond regime, this process does not likely contribute to the TA kinetics in the measured time scale (27). However, previous studies of FeFe H 2 ase-CdS constructs reported TA lifetimes in the range of 100 ns, significantly longer than the data presented here (19,20). The discrepancy may be attributed to the presence of surface ligands (not present in M. thermoaceticaCdS) which present a charge-transfer barrier, differences in CdS-H 2 ase spatial proximity, solvent effects and reorganization energies, H-bonding networks, and the relatively impaired functionality of purified enzymes under in vitro vs. in vivo conditions (28)(29)(30).…”
Section: −1contrasting
confidence: 54%
See 1 more Smart Citation
“…As hot e − relaxation in Cd-chalcogenide quantum dots occurs in the subpicosecond regime, this process does not likely contribute to the TA kinetics in the measured time scale (27). However, previous studies of FeFe H 2 ase-CdS constructs reported TA lifetimes in the range of 100 ns, significantly longer than the data presented here (19,20). The discrepancy may be attributed to the presence of surface ligands (not present in M. thermoaceticaCdS) which present a charge-transfer barrier, differences in CdS-H 2 ase spatial proximity, solvent effects and reorganization energies, H-bonding networks, and the relatively impaired functionality of purified enzymes under in vitro vs. in vivo conditions (28)(29)(30).…”
Section: −1contrasting
confidence: 54%
“…Membrane-bound NiFe H 2 ases may play a significant role as H 2 directly feeds into the WLP. Demonstrations of direct e − transfer between metal chalcogenide nanoparticles and purified H 2 ases in vitro lend credibility to this pathway's existence in complex whole cells (18)(19)(20). Alternative pathways have implicated e − transfer first to membrane-bound cytochromes, ferredoxin (Fd), flavoproteins (Fp), and menaquinones (MK) (13,14).…”
mentioning
confidence: 99%
“…For example, King et al. constructed a series of inorganic‐biological hybrid systems using cadmium telluride (CdTe) or cadmium sulfide (CdS) nanorods and purified [FeFe]‐hydrogenase derived from Clostridium acetobutylicum [3a–d] . These systems showed the performance of highly active [FeFe]‐hydrogenase [4] and achieved highly efficient light‐driven hydrogen production; however, difficulties owing to the high costs of protein purification and the high oxygen sensitivity of [FeFe]‐hydrogenase must be addressed for further improvement of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Using longer capping ligands resulted in less-efficient hydrogenase adsorption and slower electron transfer, resulting in an overall decrease in hydrogen production. A recurring theme in enzyme-nanocrystal hybrids is the critical impact of efficient and directed electron transfer on hydrogen production, where controlling ratios between enzymes and nanocrystals and selecting capping ligands that facilitate optimal nanocrystalenzyme association play key roles [137]. This high degree of tunability could be powerful in shaping the future of lightdriven enzyme catalysis, especially because enzymes can also be tuned to facilitate interactions with nanoparticles by altering surface residues around key electron transfer sites.…”
Section: Figmentioning
confidence: 99%